Environmental impacts of nitrification and nitrate adsorption in fertilized andisols in the Valle Central of Costa Rica - J.S., Reynolds-Vargas (1994)
A major scientific challenge for modern agriculture is control of off-site effects on the water resource. In the Valle Central of Costa Rica, coffee plantations may leach fertilizer-derived (Equation presented) to groundwaters, as a result of high fertilization rates (annually ~270 kg/ha as N), highly permeable and well structured Andisols, and high rates of annual runoff (>1000 mm). The objective of this study was to examine several aspects of the nitrification and (Equation presented) adsorption that control (Equation presented) leaching from these highly productive soils. Monthly collections from four Andisols indicated that soil (Equation presented) varied seasonally, with (Equation presented) accumulating to about 280 kg/ha in the upper meter of soil during the 5-month dry season. Soil (Equation presented) was reduced during wet season months, even though fertilization was confined to the wet season. During these months, soil (Equation presented) averaged about 140 kg/ha as N in the upper meter of soil, apparently reduced by wet season leaching, root uptake, and, possibly, dentrification. Field and laboratory incubations at different soil moisture and temperature regimes demonstrated how soil microflora mineralized N and nitrified (Equation presented) at relatively high rates, even at low water potentials, e.g., <−1.5 MPa. During the dry season, field incubations suggested that nitrification rates were about 30 kg/ha per month as N in the upper 20 cm of soil. Relatively large contents of (Equation presented) can be adsorbed by these allophanous Andisols, especially at low pH (up to about 5 cmol/kg at pH <3). Nitrate adsorption potentially retards leaching of (Equation presented) to groundwater; however, the effectiveness of adsorption as a protection of groundwater quality is probably limited due to high inputs of fertilizer N and to liming management of coffee soils that maintains relatively high soil pH. Additional research into the coffee N cycle and fertilizer efficiency in coffee is needed to ensure high coffee productivity and to protect aquifer water quality in the Valle Central. © 1994 The Williams and Wilkins.